Deadly progress: changes in Australian Aboriginal and Torres Strait Islander adult daily smoking, 2004–2015 - Raymond Lovett (Public Health Research & Practice, 2017)
Background: Tobacco smoking is the leading contributor to the burden of disease among Aboriginal and Torres Strait Islander Australians. Reducing tobacco use in this population is a public health priority. Precise monitoring of smoking prevalence trends is central to implementation and evaluation of effective tobacco control. The way in which trends are reported influences understanding of the extent of progress, with potential implications for policy. Our objective was to quantify absolute changes in Aboriginal and Torres Strait Islander adult (≥18 years old) daily tobacco smoking prevalence from 2004 to 2015, including comparisons with the total Australian population, and by age, sex and remoteness.